Low complexity blind selective mapping in orthogonal frequency division multiplexing: utilizing linear combination - Abdul Wahab, Aeizaal Azman; Muhammad Adnan, Nur Qamarina; Mohamad Hamzah, Firdaus (Institute of Advanced Engineering and Science, 2025)
Orthogonal frequency division multiplexing (OFDM) is a cornerstone in wireless communications for its spectral efficiency and robustness against multipath fading. However, its deployment is constrained by the high peakto-average power ratio (PAPR), which demands complex power amplifiers and increases system costs. Selective mapping (SLM) is a popular distortion less method for PAPR reduction but suffers from high computational complexity and data rate losses due to side information (SI) transmission. This paper proposes a low-complexity, blind SLM method utilizing linear combination, which reduces computational complexity by generating alternative candidate signals without additional inverse fast fourier transform (IFFT) operations. A maximum likelihood estimation (MLE)-based blind receiver recovers transmitted signals without SI, preserving data rate integrity. The proposed method achieves comparable PAPR and bit error rate (BER) performance to conventional SLM (C-SLM) while significantly reducing computational operations. Simulations demonstrate the efficiency of the method across various configurations, making it a strong candidate for next-generation communication systems like 5G and beyond.